Taxonomy of the subgenera Thermobacterium and Streptobacterium (Groups I and II) of the genus Lactobacillus - Du Toit, Margaretha (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1992.